Pengaruh Fraksi Volume Serat terhadap Sifat-sifat Tarik Komposit Diperkuat Unidirectional Serat Tebu dengan Matrik Poliester - Berli P. Kamiel, M. Budi Nur Rahman , (Jurnal Semesta Teknika, 2011)
Sugar cane fiber has not optimallybeen used as reinforcement of compositematerial. So far, bagasse has been used as  firewood-substitute, raw material for papers, and brake lining. The purpose of this study is to investigate the effect of fiber volume fraction, Vf, on tensile strength of unidirectional sugar cane fiber/polyester composites. The material being used was sugar cane fiber, 268 SHCP BQTN  polyester resin and catalyst . Fibers were soaked in alkali (NaOH) 5% for 2 hours in order to remove their impurities. Composite panels were made with a printing press and the volume fractions of the fiber were 0%, 10%, 20%, 30% and 40%. Prior to being cut into specimens, the panels were subsequenlypost-cured at a temperature of 60 0C for 4 hours. Tensile testing wa carried out according to theASTM D638 standard, and fracture area photo macrographs of selected sampleswere analysed in order to find out the characteristics of fracture. It was found out that increasing the fiber volume fraction resulted in thedecrease of tesilestrength and strain,butincrease of the modulus of elasticity . The highest average tensile strength and strain was obtained at Vf = 0% (31.44 MPa and 9,11%), and a tensile modulus of elasticity was at Vf = 20% of 426.92 MPa. The observations on the photo macrographs showed thatcomposite fracture predominantly occuredspecimens withVf = 30%, and single fracture combined withfiber pull-out was identified for those ofVf = 0%, 10%, 20% and 40%.